EVE: A tool for temporal equilibrium analysis - Gutierrez, J; Najib, M; Perelli, G; Wooldridge, M (Springer Verlag, 2018)
We present EVE (Equilibrium Verification Environment), a formal verification tool for the automated analysis of temporal equilibrium properties of concurrent and multi-agent systems. In EVE, systems are modelled using the Simple Reactive Module Language (SRML) as a collection of independent system components (players/agents in a game) and players’ goals are expressed using Linear Temporal Logic (LTL) formulae. EVE can be used to automatically check the existence of pure strategy Nash equilibria in such concurrent and multi-agent systems and to verify which temporal logic properties are satisfied in the equilibria.